Application of Aswaja Character in Religious Programs Through the Approach of B.F. Skinner with Reinforcement Model at Islamic Elementary School Nurul Bayan Sumenep - Noor Alfi Fajriyani; Maemonah Maemonah (Educan : Jurnal Pendidikan Islam, 2022)
Aswaja character education is important to instill in learners at a young age. Because with the cultivation of aswaja character education in students, it will form a character in accordance with the character of Islamic norms, and in harmony with the nation’s noble values. This research uses descriptive qualitative approach methods. The goal of this reseacrh was to see how the type of application of "Application of Aswaja Education to Religious Programs Through B.F. Skinner Approach With Reinforcement Model at Nurul Bayan Sumenep Islamic Elementary School".  The findings revealed that there are four forms of character values instilled in four programs for relegious activities at SDI Nurul Bayan Sumenep, namely the character values of tawassuth, tawazun, I'tidal, and tasamuh.  Some religious activities adopt from the NU amaliyah tradition, with the aim of instilling a sense of love in nu traditions from an early age. Reinforcement is given to learners who give rise to certain behaviors. This behavior arises starting with the provision of stimulation. If the behavior that arises is pleasant then the teacher will give rewards. If the behavior that arises is unpleasant the teacher will give educational punishment. So that the behavior decreases and disappears.